Extracorporeal Membrane Oxygenation for COVID-19: Case Report of Nine Patients - Hua, Jing; Zhang, Xin; Wang, Na; Ran, Linyu; Wang, Shengyun; Huang, Chiungwei; Gao, Wei; Qian, Chenchen; Guo, Wei; Liu, Zhongmin; Li, Qiang; Wang, Feilong (Frontiers in Medicine, 2021)
Covid-19, Coronavirus disease 2019; ARDS, Acute respiratory distress syndrome; ECMO, Extracorporeal Membrane Oxygenation; WHO, World Health Organization; ICUs, Intensive care units. Acute respiratory distress syndrome (ARDS) is a fatal comorbidity of critically ill patients with COVID-19, who often end up on respiratory support. However, the safety and effectiveness of Extracorporeal Membrane Oxygenation (ECMO) in the treatment of COVID-19 remains to be elucidated at present. Here, we report on nine patients who received ECMO due to severe SARS-CoV-2 infection in Wuhan, China. Our initial experiences suggest that carefully selecting patients, as well as management by a well-trained team, are critical to implementing ECMO in patients with COVID-19. More randomized controlled trials with larger sample sizes are needed to evaluate the usefulness of ECMO in patients with COVID-19.